Implementation of Differentiated Learning on Acid-Base Materials to Improve Learning Motivation and Critical Thinking Skills of High School Students - Musdalifah, Hainun; Wiyarsi , Antuni (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study aims to analyze significant differences in learning motivation and critical thinking skills simultaneously between students who learn with differentiated learning and those who do not, determine the effective contribution of the implementation of differentiated learning on acid-base materials to learning motivation and critical thinking skills of students simultaneously, to determine the effective contribution of differentiated learning implementation on acid-base material to high school students' learning motivation, to determine the effective contribution of differentiated learning on acid-base material to high school students' critical thinking skills, to determine the level of achievement of students' critical thinking skills in experimental and control classes. This study used a quasi-experiment model with a pretest-posttest control group design. The sample of this study consisted of two classes, namely experimental class and control class, with random sampling. The experimental class used differentiated learning, while the control class used discovery learning. Critical thinking skills data were obtained from the description test data and learning motivation data through questionnaires. MANOVA test was used to analyze differences in critical thinking skills and student learning motivation in experimental and control classes simultaneously. Test of between subject effects is used to analyze differences in each dependent variable in experimental and control classes. Partial eta square test is used to analyze the effective contribution of differentiated learning to the dependent variable. Descriptive statistics to determine the level of achievement of critical thinking skills. The results showed there were significant differences in learning motivation and critical thinking skills simultaneously and individually between students who used differentiated learning and those who did not, the effective contribution of differentiated learning on acid-base materials to critical thinking skills and student learning motivation simultaneously was 16.9% (high), the effective contribution of differentiated learning on acid-base material to students' critical thinking skills is 6. 1% (medium), the effective contribution of differentiated learning on acid-base material to student learning motivation is 12% (medium), the level of achievement of critical thinking skills in the experimental class is in the good category, while in the control class in the sufficient category.